PENERAPAN MEDIA PEMBELAJARAN HIDROKARBON BERBASIS AURORA 3D PRESENTATION UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK DI KELAS XI MIPA SMAN 1 KAMPAR - Des Syafriani; Asmadi M. Noer; Susilawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research aims to increase student learning achievement on the topic of hydrocarbon inclass XI MIPA Senior High School (SMAN) 1 Kampar. Aurora 3D Presentation was used when the teacher explained the topic being able to explain abstract concepts into concrete, one of them on the topic of hydrocarbon. The research was a kind of experiment research with pretest-posttest design. The samples of this research were the students of class XI MIPA 3 as the experimental class and students of class XI MIPA 4 as the control class. Experimental class is a class that is applied to media Aurora 3D Presentation while the control class was not. Data analysis technique which is used is t-test. Based on data analysis of data obtained tcount> ttable is 2,30 >1,67, it means  that the application of Aurora 3D Presentation as media presentation can improve student learning achievement on the topic of hydrocarbon in class XI MIPA Senior High School (SMAN) 1 Kampar, increase learning of 7,03%.